Identifikasi Kendala dan Strategi Guru dalam Pembelajaran IPAS di Sekolah Dasar - Sagitasari, Putri Aprilia; Sholihah, Husna Imro’atus; Mariyani, Anna (Universitas Muhammadiyah Magelang, 2025)
This study aims to identify the constraints faced by teachers in teaching Natural and Social Sciences (IPAS) and to analyze the strategies used to overcome them. The research employed a qualitative descriptive method with the subjects being a fifth-grade teacher, the principal, and 13 students at SD Negeri 2 Nglenkgir. Data were collected through observation, interviews, and questionnaires, then analyzed using the Miles & Huberman model. The findings reveal three main constraints: low student interest, limited instructional time, and a high administrative workload for teachers. To address these obstacles, teachers implemented creative strategies such as the use of technology-based media, ice-breaking activities, creating a conducive classroom environment, assigning additional tasks as learning extensions, and utilizing time management and digital technology for academic reports. This study affirms that teachers can adapt through practical strategies aligned with humanistic learning theory and Street-Level Bureaucracy theory. The findings of this study have implications for the importance of institutional support in providing learning facilities and reducing the administrative burden on teachers.